Forecasting Rice Production for Strategic Decision Making in Agribusiness Management: Aplication of Brown’s Double Exponential Smoothing in Batubara District - Ahmad Riyansyah; Ayu Novita Sari Pasaribu (TALENTA Publisher, Universitas Sumatera Utara, 2025)
An assessment of what will occur in the future is called a forecast. For Indonesians, rice is a staple food, and because of its most crucial role, forecasting is required to satisfy community demands. For that, we require an indicator that can use Brown's double exponential smoothing method to illustrate the rise and fall in Batu Bara District's rice production in 2021. The time series approach, which employs historical data to forecast future events, includes Brown's double exponential smoothing method. Using the parameter α, the data demonstrates a trend. The value that yields the least Mean Square Error (MSE) is the ideal parameter value. The data processing results indicate that the parameter α = 0,1 has an MSE of 362.579.150,59. The volume of rice output in 2021 is predicted to be 118.082,84 tons using the forecasting equation F_(t+m) = 117.773,25+309,5m.